Companion Mathematica notebook and experimental datasets for 'Uncovering the mechanical secrets of the squirting cucumber' - Moulton, D; Box, F (University of Oxford, 2024)
Experimental data sets and Mathematica notebooks that accompany the mathematical modelling and output presented in the PNAS publication, Uncovering the mechanical secrets of the squirting cucumber'